Switching Intention Analysis of Refrigerant Users to Breezon in South Tangerang City Using PPM and TPB - Mohammad Hamdani; Arthur Sitaniapessy; Amir Fikri (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
Currently, global warming and ozone layer damage continue to increase. Global warming has a serious and broad impact on the environment. With the spirit of creating superior and environmentally oriented products to answer the development of the refrigeration sector in facing current environmental issues, Pertamina presents Breezon MC-32 (R-1270) which is the latest generation of refrigerant from Pertamina which is environmentally friendly and can save energy, launched since December 2020 and is currently produced by Pertamina refineries in Indonesia. The purpose of this study is to analyze the intention to switch synthetic refrigerant users to Breezon using the Push-Pull-Mooring theory approach and the Theory of Planned Behavior. The results of the respondent survey used as a sample in this study were 220 respondents domiciled in South Tangerang City who use Split Wall AC. Based on the results of the study, it is known that push and pull factors have a significant positive effect on switching intentions, while mooring factors have a significant negative effect on consumer switching intentions. The factors of attitude towards behavior, subjective norms, and perceived behavior control have a significant positive effect on switching intentions. Environmental sustainability is important for AC users, and they are interested in using Breezon because it has several advantages and benefits, although there are anchoring factors that prevent AC users from switching to using Breezon. Advice from people close to them and knowledge about the product also have an important influence on AC users wanting to switch to using Breezon.